“Influencia de faces lunares en la propagación vegetativa del injerto tipo momia (pua lateral) usando el clon ccn-51 en vivero en el cultivo de cacao (theobroma cacao L.) en el distrito de morales -San Martín” - Vela Ramírez, Edward Diego (2014)
This research paper entitled "lnfluence of moon phases in the vegetative propagation of the type mummy graft (Lateral Spike) using the CCN-51 clone nursery in the cultivation of cocoa (Theobroma cacao L.), in the district of Morales - San Martín "was conducted in order to evaluate the influence of the moon phases in the process of type grafting mum and arrest CCN-51 clone in growing cacao (Theobroma cacao L.), and determine which of moon phases have greater influence on the process of grafting and arrest. This research was conducted on the property of Mr. Theobald Cubas Zamora, located in the district of Morales, province and department of San Martín, a South Latitude 06º 28 '50' West Longitude 76º 29 '30' at an altitude of 333 msnmm Statistical Design randomized complete block (RCBD) with four treatments and four replications. Field data was processed using SPSS 19 program, which was used as the P-value comparison to the F calculated confidence levels 0.01 and 0.05 and multiple range test Duncan at PS0.05. lt was used as mother to the variety Pound (seedlings) as yemera rod plant and CCN-51 clone. The grafting was developed within three days of each lunar phase and 90 days of growth in nursery phase. The variables evaluated were: percentage of grafted plants, number of outbreaks and pinned grafted plants, number of leaves on shoots sprouted graft and graft height. The results indicate that the phase of the full moon was the most important treatment comparad with other lunar phases and had greater influence on the process of grafting and arrest CCN-51 clone in the cultivation of cacao (Theobroma cacao L.) nursery phase. His influence led to an increased percentage of seizure (92%), a greater number of shoots (4.49) in grafted and pinned 90 days plants, more leaves (24.2) and higher growth graft (27.3 cm). Keywords: lnfluence, phases, propagation, vegetativa, graft, mummy, pick, lateral, cocoa, arrest, shoot, leaf.